Analysis of factors influencing the treatment burden in patients with chronic diseases complicated with psoriasis vulgaris - XU Junfang; QIN Yao; CAO Shuo; CHEN Xuemei (Pifu-xingbing zhenliaoxue zazhi, 2025)
[Objective] To investigate the current status and influencing factors of treatment burden in patients with psoriasis vulgaris and chronic diseases, providing a basis for optimizing diagnostic and treatment strategies. [Methods] A total of 158 patients with psoriasis vulgaris and chronic diseases treated at Dermatology Hospital, Southern Medical University from March 2022 to March 2024, were included in this study. The multimorbidity treatment burden questionnaire (MTBQ) was used to assess treatment burden. The differences in medication use, occupational labor intensity, and residential location were compared between patients with a moderate-to-high burden and those with low or no burden. The perceived social support questionnaire was used to evaluate social support scores, and the psoriasis area and severity index (PASI) was used to assess disease severity. Univariate and multivariate logistic regression analyses were conducted to identify factors influencing treatment burden. [Results] Among 158 patients, 116 (73.42%) reported moderate-to-high treatment burden and 42 (26.58%) reported low or no treatment burden. There were significant differences between the moderate-to-high burden group and the low or no burden group in terms of age, gender, medication types, educational level, average monthly household income per capita, medical insurance type, employment status, smoking rate, drinking rate, labor intensity, residential location, PASI score, and social support questionnaire score. Logistics regression analysis showed that social support was an independent protective factor against treatment burden (OR=0.94, 95%CI:0.90~0.99, P=0.010). The risk of treatment burden increased by 6.33 times for high-intensity laborers, while living in urban areas was an independent protective factor against the treatment burden (OR=0.14, 95%CI:0.02~0.98, P=0.040). PASI scores were not significantly associated with treatment burden (P=0.907). [Conclusions] Patients with psoriasis vulgaris complicated with chronic diseases experience a heavy treatment burden. Higher levels of social support can reduce the risk of treatment burden, while the treatment burden risk increases for individuals engaged in moderate or high-intensity labor. Urban residents have a relatively lower treatment burden. Policymakers may consider enhancing social support systems, optimizing the allocation of medical resources, and paying particular attention to the healthcare needs of those in high-intensity labor to reduce their treatment burden.